Kajian Literatur: Faktor Penyebab Kesulitan dalam Pemahaman Konsep Matematis pada Siswa - Eka Yatri, Alya; Suradi; Danial (Lattice Journal : Journal of Mathematics Education and Applied, 2025)
This study aims to analyze and identify various previous research findings related to students' difficulties in understanding mathematical concepts. This study used a literature review method with a qualitative descriptive approach. Data were obtained from 15 previous research journals published between 2020 and 2025. The results of the study indicate that students' difficulties in understanding mathematical concepts are caused by cognitive, affective, metacognitive, and pedagogical factors. Cognitive factors relate to students' inability to connect basic concepts with their application in new contexts, while affective factors include anxiety, low motivation, and lack of self-confidence in learning mathematics. In addition, low metacognitive abilities cause students to have difficulty planning, monitoring, and evaluating their thinking processes. From a pedagogical perspective, the use of learning methods that still focus on procedures and memorization also worsens students' conceptual understanding. This study emphasizes that low mathematical conceptual understanding results from the interaction of psychological factors, pedagogical factors, and the characteristics of mathematical concepts, which are abstract and hierarchical and require symbolic, visual, and verbal representational abilities, particularly in topics such as Systems of Linear Equations in Two Variables, geometry, fractions, and matrices. Penelitian ini bertujuan untuk menganalisis dan mengidentifikasi berbagai hasil penelitian terdahulu yang berkaitan dengan kesulitan siswa dalam memahami konsep matematis. Penelitian ini menggunakan metode penelitian kajian literatur dengan pendekatan deskriptif kualitatif. Data diperoleh dari 15 jurnal penelitian terdahulu yang dipublikasikan dalam kurun waktu 2020 sampai 2025. Hasil kajian menunjukkan bahwa kesulitan siswa dalam memahami konsep matematis disebabkan oleh faktor kognitif, afektif, metakognitif, dan pedagogis. Faktor kognitif berkaitan dengan ketidakmampuan siswa mengaitkan konsep-konsep dasar dengan penerapannya dalam konteks baru, sementara faktor afektif meliputi kecemasan, rendahnya motivasi, dan kurangnya rasa percaya diri dalam belajar matematika. Selain itu, kemampuan metakognitif yang rendah menyebabkan siswa kesulitan dalam merencanakan, memantau, dan mengevaluasi proses berpikirnya. Dari sisi pedagogis, penggunaan metode pembelajaran yang masih berfokus pada prosedur dan hafalan turut memperburuk pemahaman konsep siswa. Kajian ini menegaskan bahwa rendahnya pemahaman konsep matematis merupakan hasil interaksi antara faktor psikologis, pedagogis, dan karakteristik konsep matematika yang bersifat abstrak, hierarkis, serta menuntut kemampuan representasi simbolik, visual, dan verbal, khususnya pada materi seperti Sistem Persamaan Linear Dua Variabel (SPLDV), geometri, pecahan, dan matriks.